How Educational Practices Influence Students’ Motivation in Learning Foreign Languages - Ahmad Jailani (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
Motivation is the desire to attain goals. It is an important thing to be concerned in teaching and learning a foreign language. With its absence among students, it is hard for faculties to make their students reach the competences. Therefore, researches related to students’ motivation in learning foreign languages should be done to support the success of foreign language learning. As we know, many factors influencing students’ motivation in learning a foreign language. One of those, which is not explored frequently, is on the educational practices. This article discusses how educational practices such as the curriculum, the quality of teachers, and the assessment give influences to students’ motivation. From the discussion, we know that, to make students motivated, the curriculum should be challenging but not either too difficult or too easy; the teachers’ quality should meet their expectation and be upgraded; and the assessment should not be focused on cognitive only.